2016
DOI: 10.1038/cgt.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Locked nucleic acid inhibits miR-92a-3p in human colorectal cancer, induces apoptosis and inhibits cell proliferation

Abstract: MicroRNAs (miRNAs) are a type of small noncoding RNAs that have a vital role in basic biological processes such as cellular growth, division and apoptosis. A change in the expression of miRNAs can induce many diseases. Recently, the role of miRNA in some of the cancers as a tumor suppressor and oncogene has been recognized. Several studies have proved that miR-92a-3p acts as an oncogene in colorectal cancer (CRC). We studied CRC by inhibiting miR-92a-3p in SW48 cells (human colorectal cancer cell line) that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The results showed that overexpression of miR-92a significantly induced growth retardation, which implicated miR-92a as playing an inhibitory role in the growth of gastric cancer [18]. Similar results were reported in Ahmadi's study in colorectal cancer [19].…”
Section: The Potential Oncogenic and Suppressive Effect Of The Mir-17supporting
confidence: 86%
“…The results showed that overexpression of miR-92a significantly induced growth retardation, which implicated miR-92a as playing an inhibitory role in the growth of gastric cancer [18]. Similar results were reported in Ahmadi's study in colorectal cancer [19].…”
Section: The Potential Oncogenic and Suppressive Effect Of The Mir-17supporting
confidence: 86%
“…Furthermore, miR-92a-3p over-expression was shown to be related to acute myeloid leukemia [ 57 ]. Moreover, miR-92a-3p and miR-24-3p were associated with colorectal cancer [ 58 ] and nasopharyngeal carcinoma [ 59 ], respectively. miR-155-5p behaves as either an oncogene or an anti-oncogene in carcinogenesis, and miR-155-5p has been associated with various diseases including cancers, viral infections, inflammation, and cardiovascular diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it was observed that overexpression of miR-92a-3p can disrupt PI3K/Akt/mTOR pathway by targeting two negative regulatory factors of this pathway, PTEN and PHLPP [29, 31]. Different studies have reported that overexpression of miR-92a-3p is involved in the development of metastasis and correlates with survival in different malignancies [3234]. Our study shows that miR-92a-3p is significantly overexpressed in urinary cells of NMIBC progressing patients which is in concordance with its role as oncomiR.…”
Section: Discussionmentioning
confidence: 99%